Prevalence Rates of Congenital Coronary Anomalies and Coronary Variations in Adult Indian Population Using Dual-Source Computed Tomography Coronary Angiography: Analysis of Regional Distribution of Coronary Anomalies and the Need for Standardized Reporting Formats - Ganga, Kartik P.; Goyal, Aayush; Ojha, Vineeta; Deepti, Siddharthan; Sharma, Sanjiv; Kumar, Sanjeev (Indian Journal of Radiology and Imaging, 2021)
Background Congenital coronary artery anomalies (CCAA) are predominantly discovered as incidental findings on computed tomography coronary angiography (CTCA) of adults. They are rare but significant, considering their importance during endovascular or surgical interventions. This study describes the prevalence of CCAA and coronary variants (CV) in adults as identified by CTCA.Methods It is a retrospective evaluation of 7,694 CTCAs of adults performed in a tertiary care facility in North India.Results CCAA and CV were observed in a total of 9.6% of patients. The most common CV was myocardial bridging, observed in 7.1%. Anomalies of origin and course were detected in 2.3% of the patients. The frequency of these anomalies in the right coronary artery, left main, left circumflex artery, and the left anterior descending artery arteries were 1.06, 0.41, 0.03, and 0.38%, respectively. The single coronary pattern was seen in 0.05% and coronary artery fistulas in 0.03%. Scrutiny of data on Indian regional distribution revealed differing definitions and inclusion and exclusion criteria, making comparisons difficult, highlighting the need for uniform definitions as well as the need to adopt a standardized reporting template and format.Conclusion The prevalence of CCAA and CV is 9.6% in adult Indian patients undergoing CTCA. Prior knowledge of these anatomical finding can prevent a catastrophe during surgery or endovascular interventions. Hence, it is important that clinicians, as well as radiologists, are aware of these entities.
Keywords: computed tomography coronary angiography; coronary artery anomalies; coronary variations